The dropping of three zeroes from Iraqi dinar (Journal of Accounting and Financial Studies ( JAFS ), 2010)
The purpose of this research is to explain the effect of the dropping of three zeroes from Iraqi dinar on the basic role of the dinar and derivative and dynamic in transaction of Iraqi economic. the importance of this research comes from the effect of this operation on the evaluation of the exchange between the individuals of Iraqi society and the other between the Iraqi individuals and the foreign whom use the Iraqi dinar as a tool for exchange also the effect of the operation on the reserves of the Iraqi dinar the results of this research are as the following:-1-the operation of dropping of zeroes must be associated with increase of the sharing of economic sectors with the oil sector in the gross national product.2-it is necessary to do this operation after the disappearance of the world economic crises.